Transverse colon perforation due to carcinoma rectum: an unusual presentation against Laplace's law. (16th August 2013) - Sahoo, Manash Ranjan; Kumar, Anil; Jaiswal, Sunil; C, Basavaraja
Abstract : We present a case of distal large bowel obstruction, in the setting of a competent ileocaecal valve, the caecum is the most common site of perforation (for Laplace's law). We describe a case of obstruction at the rectum due to constricting carcinomatous growth, presenting with perforation of transverse colon (against Laplace's law). A 60-year-old women presented to the emergency department with acute abdominal pain. The pain was preceded by 3 days of intestinal obstruction. Clinically there was guarding and rigidity. Straight X-ray of the abdomen revealed free gas under diaphragm. Surgical exploration revealed transverse colon perforation with carcinoma of rectum. Loop transverse colostomy was performed as the patient was very sick. The patient improved slowly in the intensive care unit. To conclude, even though the caecum is the most common site for perforation in case of distal obstruction, perforation of transverse colon can occur otherwise as a unique presentation.